2011
DOI: 10.2166/wst.2011.102
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aerated rock filter geometry on the rate of nitrogen removal from facultative pond effluents

Abstract: Rock Filters are an established technology for polishing waste stabilization pond effluents. However, they rapidly become anoxic and consequently do not remove ammonium-nitrogen. Horizontal-flow aerated rock filters (HFARF), developed to permit nitrification and hence ammonium-N removal, were compared with a novel vertical-flow aerated rock filter (VFARF). There were no differences in the removals of BOD 5 , TSS and TKN, but the VFARF consistently produced effluents with lower ammonium-N concentrations (<0.3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This can eliminate high construction costs. While the pond geometry may not have indicated an effect on a pond's performance, Hamdan and Mara's comparison between horizontal and vertical pond orientation for the treatment of total Kjeldahl nitrogen (TKN) showed that the vertical-flow orientation has a better treatment performance as compared to the horizontal flow (Hamdan and Mara 2011).…”
Section: Pond Geometrymentioning
confidence: 99%
“…This can eliminate high construction costs. While the pond geometry may not have indicated an effect on a pond's performance, Hamdan and Mara's comparison between horizontal and vertical pond orientation for the treatment of total Kjeldahl nitrogen (TKN) showed that the vertical-flow orientation has a better treatment performance as compared to the horizontal flow (Hamdan and Mara 2011).…”
Section: Pond Geometrymentioning
confidence: 99%
“…The systems are also moderately inexpensive, have low energy requirements and do not require highly skilled personnel [6]. However, the VFARF system design is needed to be developed under warm climate as has been ssuggested in Hamdan and Mara [7]. Therefore, this study was conducted by using the VFARF system with low cost media which is steel slag.…”
Section: Introductionmentioning
confidence: 99%